2017
DOI: 10.1016/j.nicl.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Altered structural brain changes and neurocognitive performance in pediatric HIV

Abstract: Pediatric HIV patients often suffer with neurodevelopmental delay and subsequently cognitive impairment. While tissue injury in cortical and subcortical regions in the brain of adult HIV patients has been well reported there is sparse knowledge about these changes in perinatally HIV infected pediatric patients. We analyzed cortical thickness, subcortical volume, structural connectivity, and neurocognitive functions in pediatric HIV patients and compared with those of pediatric healthy controls. With informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 55 publications
8
38
1
Order By: Relevance
“…HIV+ children have been found to have differences in their brain structure and function, including alterations in cortical thickness, subcortical volumes, regional connectivity, and neurometabolites. 38,39 These changes have been associated with lower cognitive functioning. 38,39 Although HIV exposure having negative impacts on HIV+ and HEU children is supported in the results of our study, the assessments used throughout the…”
Section: Figurementioning
confidence: 99%
“…HIV+ children have been found to have differences in their brain structure and function, including alterations in cortical thickness, subcortical volumes, regional connectivity, and neurometabolites. 38,39 These changes have been associated with lower cognitive functioning. 38,39 Although HIV exposure having negative impacts on HIV+ and HEU children is supported in the results of our study, the assessments used throughout the…”
Section: Figurementioning
confidence: 99%
“…Some research reported that children with perinatally acquired HIV (PHIV) present more frequently than adults with central nervous system opportunistic infection resulting from HIV immunosuppression due to the vulnerability of the child's developing brain (9). Neurological manifestations in perinatally HIV infected children include cortical and subcortical structural changes (10) that is associated with neurocognitive impairments in PHIV children and is argued to contribute to the overall burden of neurodevelopmental disabilities that persist throughout childhood, adolescence, and beyond (11). Domain-specific neurocognitive impairments have been found in children with HIV even on cART (12).…”
Section: Introductionmentioning
confidence: 99%
“…20 Accumulating neuroimaging evidence suggests structural large-scale connectivity alterations not only in primary brain disorders such as Alzheimer's disease, 21,22 epilepsy, 23,24 or schizophrenia, 25,26 but also in diseases with a rather secondary influence on the central nervous system, for example, breast cancer, 27 type 1 diabetes, 28 or HIV infection. 29 Whether these changes in network architecture and effectiveness reflect the general mental burden of illness or are associated with disease-specific aspects has not been well investigated so far.…”
Section: Introductionmentioning
confidence: 99%